Rites of retaliation : civilization, soldiers, and campaigns in the American Civil War - Foote, Lorien, 1969- (Steven and Janice Brose lectures in the Civil War era., 2021)
During the Civil War, Union and Confederate politicians, military commanders, everyday soldiers, and civilians claimed their approach to the conflict was civilized, in keeping with centuries of military tradition meant to restrain violence and preserve national honor. One hallmark of civilized warfare was a highly ritualized approach to retaliation. This ritual provided a forum to accuse the enemy of excessive behavior, to negotiate redress according to the laws of war, and to appeal to the judgment of other civilized nations. As the war progressed, Northerners and Southerners feared they were losing their essential identity as civilized, and the attention to retaliation grew more intense. When Black soldiers joined the Union army in campaigns in South Carolina, Georgia, and Florida, raiding plantations and liberating enslaved people, Confederates argued the war had become a servile insurrection. And when Confederates massacred Black troops after battle, killed white Union foragers after capture, and used prisoners of war as human shields, Federals thought their enemy raised the black flag and embraced savagery. Blending military and cultural history, Lorien Foote's rich and insightful book sheds light on how Americans fought over what it meant to be civilized and who should be extended the protections of a civilized world.